Association of Operator and Hospital Experience With Procedural Success Rates and Outcomes in Patients Undergoing Percutaneous Coronary Interventions for Chronic Total Occlusions: Insights From the Blue Cross Blue Shield of Michigan Cardiovascular Consortium. (August 2020) - Zein, Rami; Seth, Milan; Othman, Hussein; Rosman, Howard S.; Lalonde, Thomas; Alaswad, Khaldoon; Menees, Daniel; Daher, Edouard; Mehta, Rajendra H.; Gurm, Hitinder S.
Abstract : Background: An inverse relationship has been described between procedural success and outcomes of all major cardiovascular procedures. However, this relationship has not been studied for percutaneous coronary intervention (PCI) of chronic total occlusion (CTO). Methods: We analyzed the data on patients enrolled in Blue Cross Blue Shield of Michigan Cardiovascular Consortium registry in Michigan (January 1, 2010 to March 31, 2018) to evaluate the association of operator and hospital experience with procedural success and outcomes of patients undergoing CTO-PCI. CTO-PCI was defined as intervention of a 100% occluded coronary artery presumed to be ≥3 months old. Results: Among 210 172 patients enrolled in the registry, 7389 (3.5%) CTO-PCIs were attempted with a success rate of 53%. CTO-PCI success increased with operator experience (45% and 65% in the lowest and highest experience tertiles) and was the highest for highly experienced operators at higher experience centers and the lowest for inexperienced operators at low experience hospitals. Multivariable logistic regression models (with spline transformed prior operator and institutional experience) demonstrated a positive relationship between prior operator and site experience and procedural success rates (likelihood ratio test=141.12, df=15, P <0.001) but no relationship between operator and site experience and major adverse cardiac event (likelihood ratio test=19.12, df=15, P =0.208). Conclusions: Operator and hospital CTO-PCI experiences were directly related to procedural success but were not related to major adverse cardiac event among patients undergoing CTO-PCIs. Inexperienced operators at high experience centers had significantly higher success but not major adverse cardiac event rates compared with inexperienced operators at low experience centers. These data suggested that CTO-PCI safety and success could potentially be improved by selective referral of these procedures to experienced operators working at highly experienced centers. Abstract : Supplemental Digital Content is available in the text.